The cronaca di Partenope - Caracciolo, Bartolomeo, d. 1362.
1 online resource.
Keywords: Narrating the history of Naples from its foundation in early antiquity to the year 1343, the Cronaca di Partenope was the first chronologically comprehensive history of the city and one of the earliest works of any genre composed in the Neapolitan vernacular. Drawing on earlier-medieval texts and a healthy dose of legend, it is a prime witness to Neapolitan identity and memory in the later Middle Ages and an important example of southern Italian civic historiography. This volume offers the first critical edition of the text, accompanied by an extensive introduction that establishes its author, date, historical context, source materials, and later fortunes, including its significant influence on the subsequent development of local historiography